2014
DOI: 10.3357/asem.3787.2014
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Relative Humidity Impacts Low-Intensity Exercise in the Heat

Abstract: Nonevaporative and respiratory heat loss mechanisms failed to offset decreased sweat evaporation. Nonlinear increases in Tre appeared to catalyze responses in most other variables, which demonstrated similar but temporally delayed patterns. Under these circumstances, an RH threshold for increased thermal strain plausibly existed between 55-70RH; environmental characteristics indicated the threshold occurred not where heat stress became uncompensable, but instead where Tre surpassed the "balance point," trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
4
26
0
2
Order By: Relevance
“…The higher the relative humidity, the lower the heat transfer by perspiration evaporation. Therefore, hot and humid environments impose greater thermal strain by declining evaporative heat losses (Moyen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the relative humidity, the lower the heat transfer by perspiration evaporation. Therefore, hot and humid environments impose greater thermal strain by declining evaporative heat losses (Moyen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Moyen et al 12 reported a greater heat storage and body temperatures at the higher end of the RH (55–70%) range even at a much lower exercise intensity.…”
Section: Introductionmentioning
confidence: 87%
“…More recently, the impact of a wider range of RH on the capacity to exercise was investigated at low 12 (5 RH levels) and moderate 13 (4 RH levels) intensity where it was concluded that exercise capacity was compromised at the higher end of the RH range when exposed to a hot (35°C), 12 and warm 13 (30°C) environment, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High humidity decreases the efficiency of cooling by decreasing the evaporation from the skin surface [10;12]. This leads to failure of cooling the body [13]. Further, the body responds by more sweating.…”
Section: Resultsmentioning
confidence: 99%